GENERATING GREEN ENTREPRENEURIAL INTENTION THROUGH ENVIRONMENTAL ATTITUDE - Nuringsih, Kartika; Maupa, Haris; Patricia, Vivian (International Journal of Application on Economics and Business, 2023)
In line with the achievement of sustainable development goals (SDGs), environmentally friendly business is a new challenge in carrying out entrepreneurial activities. Research on the relationship between environmental attitudes and the formation of student intentions in green entrepreneurship is necessary. Entrepreneurship students at the Faculty of Economics and Business, Universitas Tarumanagara, were involved as respondents (n = 280) using a convenience sampling technique. The purpose of this study was to determine students' intentions in green entrepreneurship activities by considering environmental attitude variables proxied through the New Ecological Paradigm (NEP) in the preparation of instruments. The results of the validity test showed that only 10 indicators could be maintained as a measure of environmental attitudes with a Cronbach’s Alpha of 0.892 and a composite reliability of 0.911 so that both were in the satisfactory category. The results of structural regression testing show a significant effect of environmental attitudes on green entrepreneurship intentions at a significance level of 5 percent. R-square of 24.60 percent indicates the large contribution of environmental attitudes to this intention. The mechanism of the relationship between attitudes and intentions is in accordance with the theory of planned behavior while the transformation in the aspect of environmental sustainability is in line with the triple bottom line theory. Based on these results, it can be adapted to an educational approach or involving stakeholders in an entrepreneurship learning approach as a support for achieving Indonesia's SDGs in 2030.